2006
DOI: 10.1038/nature05225
|View full text |Cite
|
Sign up to set email alerts
|

Real-time observation of trigger factor function on translating ribosomes

Abstract: The contribution of co-translational chaperone functions to protein folding is poorly understood. Ribosome-associated trigger factor (TF) is the first molecular chaperone encountered by nascent polypeptides in bacteria. Here we show, using fluorescence spectroscopy to monitor TF function and structural rearrangements in real time, that TF interacts with ribosomes and translating polypeptides in a dynamic reaction cycle. Ribosome binding stabilizes TF in an open, activated conformation. Activated TF departs fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
311
4

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 197 publications
(329 citation statements)
references
References 41 publications
14
311
4
Order By: Relevance
“…Thus, even for domains exhibiting the simplest possible folding behaviour on the ribosome, slow-translating codons can in certain circumstances affect cotranslational behaviour in different ways depending on the context. We note in addition the interesting result that molecular chaperones, such as trigger factor 46 , can serve as a cause of non-monotonic changes in domain stability 47 because of their binding to the unfolded ensemble 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, even for domains exhibiting the simplest possible folding behaviour on the ribosome, slow-translating codons can in certain circumstances affect cotranslational behaviour in different ways depending on the context. We note in addition the interesting result that molecular chaperones, such as trigger factor 46 , can serve as a cause of non-monotonic changes in domain stability 47 because of their binding to the unfolded ensemble 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Ribosome Associated Chaperones translational folding (Agashe et al, 2004;Kaiser et al, 2006;Kramer et al, 2009). This provides sufficient time to the elongating polypeptide to receive its entire structural information requisite for the productive folding to begin.…”
Section: Figure 2: the Major Components Of The Proteostasis Network (mentioning
confidence: 99%
“…The interplay of TF with other RPBs on the ribosome is not clear as well, as it has been reported that TF binds to and dissociates from ribosomes very slowly [21][22][23] , such that stably bound TF might interfere with the binding of other RPBs.…”
mentioning
confidence: 97%